PERBEDAAN SKALA PADA SUMBU KOORDINAT KARTESIUS: APA DAMPAKNYA DALAM PEMBELAJARAN INTEGRAL TENTU? - Afgani, Muhammad Win; Paradesa, Retni (Mathematics Education Journal, 2019)
The aim of this study was to investigate the effect caused in learning of finite integral when a lecturer give a problem about finding area below a graph of the function with two partitions which the scale on Cartesian coordinate of x-axis different with y-axis. This research type was descriptively qualitative. The subject of this study was 32 undergraduate students majoring in mathematics education that attend integral calculus class at one universities in Palembang. In this study, the 32 students was formed become 6 groups. Instrument in this study was two problems that discussed by them in group. The data was collected by documentation of students’ worksheet, observation, and interview. The result showed the effect on students, that is, they seen try to construct their mathematics knowledge by themselves first, communicate unexpected ideas before, and can think critically on the given problem. The positive effects showed up because the given problem to them related with some concepts.